A sporadic pediatric case of a spinal dumbbell-shaped epithelioid malignant peripheral nerve sheath tumor with a novel germline mutation in SMARCB1: a case report and review of the literature - Qi, Maoyang; Jiang, Nan; Duan, Wanru; Chen, Zan (Frontiers in Neurology, 2023)
It is believed that malignant peripheral nerve sheath tumors have a poor prognosis and are usually caused by germline mutations in the SMARCB1/INI-1 gene. However, these tumors are rarely found in the spine. This case describes a 3-year-old boy with a lumbosacral dumbbell-shaped epithelioid malignant peripheral nerve sheath tumor. By immunohistochemistry, a complete absence of the SMARCB1/INI-1 protein was shown. Genetic testing revealed a novel germline mutation in the SMARCB1/INI-1 gene in the patient and his father, which was regarded as a “second-hit loss”. After radical resection of the tumor, no suspected metastasis occurred in a one-year follow-up. This case report provides the novel genetic research results of the spinal dumbbell-shaped malignant peripheral nerve sheath tumors. A literature review highlighted that radical resection combined with radiotherapy and chemotherapy may be necessary to achieve local control for recurrence.